SENI BATIK UNTUK MENINGKATKAN KREATIFITAS, PRODUKTIFIAS, DAN KOMPETENSI ANAK PANTI ASUHAN AT-TAQWA - Faozi, Achmad -; Dzaky, Fauzan Abiyyu; Sukmawati, Dian Sadat; Sari, Khofifah -; Pangestika, Indri - (Admisi dan Bisnis, 2019)
As the times progressed, soft skills training to improve the creativity of the younger generation began to decrease. The younger generation tends to be more concerned with gadgets and games. This makes the younger generation tend to be lazy to think, lazy to move, lazy to be creative so that it becomes someone who has low soft skills and does not have any competence. The student creativity program (PKMM) at the At-Taqwa orphanage was held to enhance creativity by means of batik training, media promotion with CorelDraw, and marketing training. The purpose of the Creative Youth program is to improve the creativity, productivity and competence of children in the At-Taqwa orphanage so as to produce useful benefits for the welfare of the Orphanage. At-Taqwa Orphanage located in Meteseh Sub-District, Tembalang Sub-District, Semarang City houses 172 children from elementary school to college. The daily conditions of the orphanage children are formal schools and recitation. The results obtained from the PKMM program are that At-Taqwa orphanage children can develop batik artistic creativity and market it so that the benefits obtained can benefit the welfare of the At-Taqwa orphanage. The development of creativity by batik can increase productivity, and competence for At-Taqwa orphanage children